Analisis User Experience pada Aplikasi Perangkat Bergerak Kwikku dengan User Experience Questionnaire dan Heuristic Evaluation - Wahid Hasyim; Ismiarta Aknuranda; Khalid Rahmadan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Kwikku is a platform for Generation Z that collaborates between readers and content creators so thatKwikku users can enjoy various interesting and quality content ranging from novels, webtoons andarticles. Kwikku is also equipped with social media features that can support content creators tocommunicate directly with readers and promote their work. Based on brief interviews, reviews on thePlaystore, and observations, several problems were found that could reduce the value of the userexperience on the Kwikku mobile application. To find out the level of user experience on the Kwikkumobile application and understand the problems in depth, data collection and analysis were carried outusing the User Experience Questionnaire (UEQ) and Heuristic Evaluation (HE). After the analysis hasbeen carried out, the process of making improvement design recommendations is also carried out basedon the recommendations that have been obtained from the evaluators. Based on the results of the userexperience analysis on the old design, it was found that the user experience level on the Kwikku mobileapplication had a good value. This is evidenced by the benchmark results on the UEQ in the aboveaverage, good and excellent categories with an average of each scale, namely 1.55 (Attractiveness),1.83 (Perspicuity), 1.58 (Efficiency), 1.39 (Dependability), 1.95 (Stimulation), and 1.65 (Novelty). Forthe results of the evaluation using HE, the evaluators involved found 25 total problems related tousability and user experience and were also given recommendations for improvement for each problem.